The role of social media as evidence in asylum procedures in Iceland - Thorkelsdottir, N (2021)
The role of technology in border control has grown steadily in recent years. While smart border technology has become commonplace in many states, the increasing popularity of social media amongst migrant populations offers immigration authorities unprecedented opportunities to access publicly available data on asylum applicants. Although this novel vetting technique has been criticised by human rights activists as invasive and unfair, little academic research exists on the extent to which social media content is exploited as a source of evidence in asylum procedures. The purpose of this study is to address this gap by examining how social media and open-source data shapes the evidentiary assessment in asylum cases in Iceland. Based on eight in-depth interviews with Icelandic immigration officials and legal representatives of asylum applicants, I examine the extent to which social media analyses are carried out and their relevance compared to other sources of evidence. The findings of the study suggest that while social media analysis is used on a regular basis in asylum procedures in Iceland, caseworkers face various structural, personal and bureaucratic hurdles in practice. It is argued herein that due to personal experiences and attitudes towards social media, caseworkers generally consider the evidentiary value of social media too weak to be routinely turned into direct evidence.